Recursos hídricos da chapada do Araripe - Mendonça, Luiz Alberto Ribeiro (2001)
The objectives of this research were to understand the aquifers of the Araripe Plateau, quantify their resources, and assess their vulnerability to pollution. In order to address the lack of hydrologic and hydrogeologic data, methods from various areas were employed (hydrogeology, hydrochemistry, isotope hydrology, soil science, ecology and numerical modeling). Results are interpreted in a synoptic way. We performed (i) geologic analysis, (ii) chemical and isotopic analyses (O-18, C-13, H-3 and C-14) of water samples, (iii) studied organic material in soils (important to recharge) using N-15 and C-13, (iv) determined the capacity of infiltration for soils with different vegetation using the GREEN and AMPT model, (v) performed MODFLOW and MODPATH simulations of groundwater flow, and (vi) vulnerability study (FOSTER and HIRATA). In this fashion, an intimate relationship between hydrology, climate and ecology was verified for the Araripe Plateau. In the eastern section, with forests and elevated rainfall, waters of the Upper Aquifer System are young (residence time ≈ 180 years) and are derived from present day rainfall, whereas in the western section, with low rainfall and sparse vegetation, paleo-waters (pmC ≈ 25,5, ≈10.932 years) are found, identified by its colder pleistocenic climate (18O ≈ -5 ‰). In the first area, recharge is estimated to be ≈ 4 % of annual rainfall. However, for areas of deforestation, soil analyses indicate a reduction in the infiltration capacity to only 20 %, illustrating the strong influence of changes in vegetation on the water balance (and the discharge of springs) of the Plateau. MODFLOW simulations calculate for the Upper Aquifer System permanent reserves of 13*109 m3/year, regulating reserves of 21,4*106 m3/year, and a deep percolation, through fractures in the aquiclude Santana, to the Cariri Valley of 3*105 m3/year. With respect to vulnerability, the eastern section is moderate, with exception of the fault of Jardim which is highly vulnerable. The western section of the Araripe Plateau presents low vulnerability, but increasing to moderate in the area of the wells Serrolandia I and II. The ponds (“barreiros”) of the Plateau are of very poor sanitary condition and represent critical spots for aquifer pollution.